2008
DOI: 10.1068/c2g
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Capacity: Explaining Local Commitment to Climate-Change Policy

Abstract: Introduction Climate change is an environmental problem with considerable social, economic, and ecological risks (Scheraga and Grambsch, 1998). The thermometric instrumental record indicates that the global average surface temperature is increasing, and is up by about 0.6 8C in the last one hundred years. Proxy data from ice cores and tree rings suggest that the`abrupt' warming trend of the 20th century is`unique' by historical standards (North, 2003). The impacts of temperature change are many, and include co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
201
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(213 citation statements)
references
References 37 publications
8
201
4
Order By: Relevance
“…Local economic landscapes have also been found to influence political will to engage in climate change policies (Bulkeley and Betshill, 2003;Bulkeley and Kern, 2006;Elliott et al, 1997;Lorenzoni et al, 2007;O'Connor et al, 2002;Zahran et al, 2006;Zahran et al, 2008a;Zahran et al, 2008b). Thus the areas which contribute most to the climate change problem in terms of industrial structure and per capita carbon emissions are least likely to be involved in voluntary climate protection schemes Zahran et al, 2008a;Zahran et al, 2008b).…”
Section: Collective Interest and Drivers Of Climate Change Actionmentioning
confidence: 99%
See 4 more Smart Citations
“…Local economic landscapes have also been found to influence political will to engage in climate change policies (Bulkeley and Betshill, 2003;Bulkeley and Kern, 2006;Elliott et al, 1997;Lorenzoni et al, 2007;O'Connor et al, 2002;Zahran et al, 2006;Zahran et al, 2008a;Zahran et al, 2008b). Thus the areas which contribute most to the climate change problem in terms of industrial structure and per capita carbon emissions are least likely to be involved in voluntary climate protection schemes Zahran et al, 2008a;Zahran et al, 2008b).…”
Section: Collective Interest and Drivers Of Climate Change Actionmentioning
confidence: 99%
“…Despite the absence of Federal government engagement with climate change policy, 565 municipal governments have currently signed up to CCP (ICLEI, 2011). Studies have found involvement to be linked to local environmental issues such as air quality (Betshill, 2001;Lindseth, 2004), whilst Zahran et al (2008a;2008b) found that factors related to a municipal area's geographic location and socioeconomic structure variously motivated or discouraged engagement with the programme.…”
Section: Local Government Action On Climate Changementioning
confidence: 99%
See 3 more Smart Citations